Antioxidant activity and degradation kinetics of astaxanthin extracted from Penaeus sinensis (Solenocera crassicornis) byproducts under pasteurization treatment. (December 2021) - Jia, Zhe; Xu, Yan; Wang, Jiaxing; Song, Ru
Abstract: The lipid oxidation of soybean oil or peanut oil under accelerated oxidation was retarded after addition of non-saponification (N-Asta) or saponification astaxanthin (S-Asta) derived from Penaeus sinensis by-products, determined by lower malondialdehyde and peroxide value as compared with the oil controls. S-Asta or N-Asta degradation in soybean oil or peanut oil fit well to first order model. Further, the soybean oil or peanut oil containing S-Asta demonstrated lower lipid oxidation as compared to those with N-Asta addition. The thermal stability of S-Asta was further evaluated under 60–90 °C pasteurization. Significant decreases of scavenging hydroxyl radical and superoxide anion, and Asta isomers concentrations were found for S-Asta under 90 °C pasteurization; whereas the antioxidant activity of S-Asta was largely restored under 60–70 °C pasteurization. The degradation kinetics of all tans, 9-cis and 13-cis Asta, as well as Asta stereoisomers in S-Asta fit to zero order kinetics, and well described by the Arrhenius equation. The highest and lowest activation energy values of 164.83 ± 14.87 kJ/mol for all trans Asta and 17.63 ± 0.99 kJ/mol for 3S, 3′R Asta suggested their highest and the lowest pasteurization stabilities. By comparison, 13-cis, 3S, 3′S, and 3R, 3′R showed similar thermal stabilities under pasteurization. Graphical abstract: Image 1 Highlights: Soybean oil or peanut oil added with natural astaxanthin showed lower lipid-oxidation. Non- or saponified astaxanthin degradation in plant oils fit to first order models. Saponified astaxanthin isomers degradation fit to zero order model in pasteurization. 60~70 °C could be a safe pasteurization temperature range for natural astaxanthin.